Fresno-Merced Counties Legal Services: Baby Shower for Stephanie Leifer - Watkins, Howard::::::::: (1979)
Mary Ludy, ? Joanne Cordova, Michael Kanz, Leroy Cordova, Janie Munoz, Eddie Mae Lomack, Verletz Hooks, William Leifer Potluck in office library